Dysmenorrhoea presentation in Herlyn-Werner-Wunderlich syndrome: A case study - Malik, Maryam Noor; Ara, Gulshan; Akhtar, Tasneem; Naeem, Humera (Journal of the Pakistan Medical Association, 2025)
Herlyn-Werner-Wunderlich syndrome is a rare congenital anomaly characterized by uterus didelphys, obstructed hemi-vagina, and ipsilateral renal agenesis. This study aims to present a case of Herlyn-Werner-Wunderlich syndrome seen at Shifa International Hospital in Islamabad, Pakistan, in March 2024. A 32-year-old married woman who presented with dysmenorrhoea for two years and cyclic abdominal pain. Abdominal examination revealed a tender mass in the right iliac fossa. Ultrasound showed uterus didelphys, absent right kidney, a distended endometrial cavity with complex fluid, and a pelvic adnexal cyst. MRI suggested differentials including exophytic leiomyoma, adnexal cyst, or endometriosis. She was planned for hysterectomy and myomectomy. Intraoperatively, two separate uterine bodies with individual adnexa were identified, confirming Herlyn-Werner-Wunderlich syndrome. Both the uteri were preserved. The patient was discharged after two days and advised to undergo a hysterectomy at the age of 40. Atypical presentation with dysmenorrhoea and abdominal pain can delay diagnosis, increasing risk of complications like infertility and endometriosis. Keywords: Dysmenorrhoea; Müllerian ducts; Uterus.